A Comparative Science-Based Viability Assessment Among Current and Emerging Hydrogen Production Technologies - Yehia F. Khalil (Applied Sciences)
This research undertakes a comparative analysis of current and emerging hydrogen (H2) production technologies, evaluating them based on quantitative and qualitative decision criteria. The quantitative criteria include cost of H2 production (USD/kg H2), energy consumption (MJ/kg H2), global warming potential (kg CO2-eq/kg H2), and technology energy efficiency (%). The qualitative criteria encompass technology readiness level (TRL) and availability of supply chain materials (classified as low, medium, or high). To achieve these objectives, an extensive literature review has been conducted, systematically assessing the selected H2 production technologies against the aforementioned criteria. The insights synthesized from the literature provide a foundation for an informed, science-based evaluation of the potentials and techno-economic challenges that these technologies face in achieving the 1-1-1 goal set by the U.S. Department of Energy (DOE) in 2021. This target aims for a H2 production cost of USD 1/kg H2 within one decade (by 2031), including costs associated with production, delivery, and dispensing at H2 fueling stations (HRSs). Also, the DOE established an interim goal of USD 2/kg H2 by 2026. This research concludes that among the examined H2 production technologies, water electrolysis and biomass waste valorization emerge as the most promising near-term solutions to meet the DOE’s goal.